1993
DOI: 10.1063/1.465303
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic energies of the ground state of the hydrogen molecule

Abstract: Relativistic corrections, Born-Oppenheimer energies and adiabatic corrections are computed for R < 12.0 bohr for the electronic ground state of the hydrogen molecule. The Born-Oppenheimer potential is slightly lower than ever reported. The problem of linear dependencies in the basis set is removed and the same set is used for all internuclear distances which assures continuity of the results. The radiative corrections are evaluated approximately and-for that purpose-the polarizability of the molecule is also c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
231
4
4

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(253 citation statements)
references
References 27 publications
14
231
4
4
Order By: Relevance
“…Further tests performed on a set of 30 closedshell molecules (see Fig. 4 [35][36][37], with E GM evaluated from sc-GW , G 0 W 0 @HF, and G 0 W 0 @PBE. PBE total energies are included for comparison.…”
mentioning
confidence: 99%
“…Further tests performed on a set of 30 closedshell molecules (see Fig. 4 [35][36][37], with E GM evaluated from sc-GW , G 0 W 0 @HF, and G 0 W 0 @PBE. PBE total energies are included for comparison.…”
mentioning
confidence: 99%
“…We presented the first full calculation of photon-energy dependent Raman association cross sections including all rovibrational resonances associated with the intermediate states, based on the accurate electronic potential energy surfaces and properties computed by Wolniewicz and Staszewska. [18][19][20][21] We compared the exact results with those of the Placzek-Teller approximation and we showed that …”
Section: Discussionmentioning
confidence: 99%
“…The ab initio potential energy curves and electronic dipole transition moments are taken from calculations by Wolniewicz and Staszewska. [18][19][20][21] We use the vibrationally resolved lifetimes from the work by Fantz and Wu¨nderlich 22 where the sum of the initial state energy and the energy of the incoming photon exceeds the dissociation limit of an intermediate electronic state, we use the Green function absorbing boundary condition (ABC) method [23][24][25] to prevent the matrix in eqn (10) from becoming singular. The ABC method consists of replacing the constant ½G m by an r-dependent function g(r), thus effectively augmenting the potential V nO (r) with a negative imaginary potential which absorbs the wave function in the physically non-relevant outer region.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of their attractive features is the capability of incorporating finite nuclear mass/isotope and spin statistic effects directly into the electronic wave-function, in a contrast with BO treatments where these finite-mass effects are usually incorporated as corrections, either adiabatic or non-adiabatic, to the electronic energies only (see, e.g., Ref. 16). In fact, approaches going beyond the BO approximation and enabling a simultaneous description of electrons and nuclei are very useful when the nuclear de-localization has a marked influence onto the electronic wave-function itself (e.g., proton-coupled electron transfer processes).…”
Section: Introductionmentioning
confidence: 99%